2001
DOI: 10.1016/s1383-5718(01)00165-6
|View full text |Cite
|
Sign up to set email alerts
|

DNA damage and repair in Arabidopsis thaliana as measured by the comet assay after treatment with different classes of genotoxins

Abstract: The three protocols of the comet assay A/N, A/A and N/N were for the first time applied to the plant species Arabidopsis thaliana. The purpose of the experiments was to establish conditions for genotoxic exposure causing DNA damage in Arabidopsis nuclei. This is required for comprehensive gene expression profiling with the intention to screen for genes involved in response of Arabidopsis cells to genotoxic stress.Five chemicals belonging to different classes of mutagens (the monofunctional alkylating agents N-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
98
3
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(109 citation statements)
references
References 26 publications
2
98
3
1
Order By: Relevance
“…After 30 min of incubation, these plants were also briefly dried and frozen. The preparation of the comet slides was performed according to Menke et al (2001) and stained with 3× GelRed Nucleic Acid stain (Biotium, Hayward, CA, USA) diluted in 0.1 M NaCl. The comets were observed and images were taken on an AXIO Imager Z1 fluorescence microscope with an AXIOCam MRm (Carl Zeiss, Jena, Germany).…”
Section: Methodsmentioning
confidence: 99%
“…After 30 min of incubation, these plants were also briefly dried and frozen. The preparation of the comet slides was performed according to Menke et al (2001) and stained with 3× GelRed Nucleic Acid stain (Biotium, Hayward, CA, USA) diluted in 0.1 M NaCl. The comets were observed and images were taken on an AXIO Imager Z1 fluorescence microscope with an AXIOCam MRm (Carl Zeiss, Jena, Germany).…”
Section: Methodsmentioning
confidence: 99%
“…In Arabidopsis, bleomycin triggers a DSB stress response (Menke et al, 2001;Tamura et al, 2002;Chen et al, 2008), whereas hydroxyurea induces a replication stress response (Ferreira et al, 1994;Roa et al, 2009). Treating wild-type and Whirly mutant plants with bleomycin (see Supplemental Figure 7 online) or hydroxyurea (see Supplemental Figure 8 online) did not result in an increase in plastid or mitochondrial MHMR.…”
Section: The Dna Rearrangements Are Induced Mainly By Stresses Targetmentioning
confidence: 98%
“…A radiomimetic agent, bleomycin, which is known to induce SSBs and DSBs (Menke et al 2001), was used because of its versatility and low cellular toxicity. Molinier et al (2005) also reported the enhancement of the somatic HR frequency and the up-regulation of the HR-related genes with the treatment of bleomycin in Arabidopsis.…”
Section: Discussionmentioning
confidence: 99%
“…Recent works of DNA repair-related plant genes involved in response to treatment with DNA damaging agents revealed that the induction level of AtRAD51 gene is one of the best among the up-regulated genes that respond to DNA damage (Chen et al 2003;Molinier et al 2005). In order to investigate the DNA damage response of AtRAD51 promoter, a radiomimetic bleomycin, which is known to induce mostly DSBs (Menke et al 2001), and the UV-B radiation, which is reported to result in increased frequencies of homologous recombination in plant (Ries et al 2000), were employed as DNA damaging agents. Using transgenic Arabidopsis and tobacco plants harboring AtRAD51 promoter-reporter fusion genes, we investigated the expression pattern of the AtRAD51 promoter.…”
mentioning
confidence: 99%